PENEGAKAN HUKUM TERHADAP AKSI UNJUK RASA MAHASISWA YANG BERUJUNG ANARKIS DI KOTA SAMARINDA - Baso Irwadi (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT A demonstration or demonstration ("demo") is a protest movement conducted by a group of people in public.The police have the authority to maintain the demonstration so that the demonstration runs smoothly, in an orderly and safe manner in accordance with the purpose of the demonstration. The condition that often occurs on the ground is that demonstrations that initially proceed well and then turn into riots or anarchist acts carried out by protesters sometimes even lead to clashes between protesters and security forces (police). If the situation is considered to have a tendency to disrupt the public interest, then the action taken by the police as a security officer refers more to the security aspect. The problem raised in this paper is how is the law enforcement carried out by the police against student demonstrations which lead to anarchists in Samarinda City and what are the inhibiting factors in handling student demonstrations that lead to anarchists in Samarinda City.This type of research used in this study is a type of empirical legal research, which is a legal research method that uses empirical facts taken from human behavior, with a qualitative approach.The results showed that the handling by law enforcers, in this case, was the police of Kudusinda when a demonstration that led to anarchism in Samarinda City was carried out through security by Dalmas. The stages are Stages of an orderly situation (Green), Stages of an orderly situation (Yellow), Stages of an unlawful situation (Red). While the inhibiting factors in handling internal and external factors.